Health-Promoting Effects of Black Tea: A Narrative Review of Clinical Trials - Yusuf Yilmaz (International Journal of Food Science)
Black tea, a popular beverage, is rich in polyphenols. However, thorough analyses of clinical trial evidence supporting its health benefits are lacking. This narrative review is aimed at addressing this knowledge gap by synthesizing findings across pivotal clinical domains and identifying critical areas for further investigation. A comprehensive search of PubMed/MEDLINE, PubMed Central, Scopus, Web of Science, and Google Scholar was performed for English-language papers from January 1990 to July 2024, focusing on cardiovascular and metabolic health, as well as cognitive function. Findings from clinical trials indicated that consuming black tea regularly enhances endothelial and vascular health, notably by improving flow-mediated vasodilation. These advantages are largely due to the tea’s antioxidant, anti-inflammatory, and gut microbiota–modulating effects, including the promotion of beneficial bacterial species such as Flavonifractor plautii. Effects on metabolic health, such as lipid profiles and glucose metabolism, were inconsistent. However, black tea was linked to improved cognitive function, especially attention and alertness, likely due to caffeine and L-theanine. Despite these promising results, further research is needed to overcome limitations like small sample sizes and short study durations. Future studies should be aimed at standardizing black tea preparations to optimize health benefits.